Syeikh Al-'Uṡaimin’s Views on the Institution and System of Education - Hasan Asari; Abdul Mukti; Sopian Sinaga; Rahmadi Ali (UIN Sunan Ampel Surabaya, 2022)
This study aims to examine the educational thinking of Sheikh al-'U'ṡaimin related to educational institutions and systems and their relevance to contemporary Islamic education. The research method used is the character study research method. This research is library research with qualitative type. The research data was obtained from the works of Sheikh al-'U'aimin and the works of others related to Sheikh al-'U'aimin. In analyzing the existing data, an interpretation method is adopted, namely an effort to achieve a correct understanding of the facts, data and symptoms. The final result of this research shows that the Sheikh proposed a new educational pattern formulation. The purpose of education according to the Shaykh is to eliminate the ignorance of students and society in general and obtain happiness in the world and the hereafter and maintain the religion of Allah. The educator is a noble profession that demands good competence and a sense of responsibility for the development of the potential of students. Meanwhile, successful students are those who adorn themselves with noble manners and morals and are consistent in treading the path of the claimant of knowledge. As for the method of education, an educator is expected to have creativity in teaching so that students feel comfortable.